2016
DOI: 10.1590/18069657rbcs20160067
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Acid Extraction to Analyze K and Mg Reserves in the Clay Fraction of Soils

Abstract: Extraction of K and Mg with boiling 1 mol L -1 HNO 3 in an open system for predicting K and Mg uptake by plants is a method of low reproducibility. The aim of this study was to compare the extraction capacity of different acid methods relative to hydrofluoric acid extraction for K and Mg. A further objective was to develop a chemical extraction method using a closed system (microwave) for nonexchangeable and structural forms of these nutrients in order to replace the traditional method of extraction with boili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Based on previous work, this one of the cubic polynomial model has been justified, for example, Villwock et al (2004), in which the calibration equation model that had a coefficient of determination closest to 1 was the cubic polynomial model. For Batista et al (2016), the cubic polynomial equations had a calibration coefficient close to the ideal for 5 soil types with different textural classes. Regardless of the soil with a clayier texture having shown less efficiency in the cubic model, it still had a good calibration adjustment.…”
Section: Resultsmentioning
confidence: 86%
“…Based on previous work, this one of the cubic polynomial model has been justified, for example, Villwock et al (2004), in which the calibration equation model that had a coefficient of determination closest to 1 was the cubic polynomial model. For Batista et al (2016), the cubic polynomial equations had a calibration coefficient close to the ideal for 5 soil types with different textural classes. Regardless of the soil with a clayier texture having shown less efficiency in the cubic model, it still had a good calibration adjustment.…”
Section: Resultsmentioning
confidence: 86%
“…Determination of soil pH was carried out in a 0.01 mol/L CaCl 2 solution; exchangeable P, K, Ca, and Mg by the ion exchange resin method; exchangeable Al by 1 mol/L KCl; and potential acidity (H + Al) by the SMP buffer solution. Cation exchange capacity was the sum of exchangeable Ca, Mg, K, Na, Al, and H. Total elements were determined by microwave-assisted digestion with nitric and hydrochloric acid (EPA 3051A method) followed by ICP-AES (EPA 6010D method), according to EPA SW-846 except for K, which was determined by flame photometry after digestion by the EPA 3051A method [27].…”
Section: Sampling and Analyzing Soil And Saprolitementioning
confidence: 99%
“…Although Ferralsols have low cation contents, previous studies have reported the presence of structural K and non-exchangeable K forms (Mielniczuk, 1977;Goedert, 1983;Martins et al, 2004;Faria et al, 2012;Alves et al, 2013). Structural K is usually associated with the silt fraction of Ferralsols, in recalcitrant minerals such as mica and feldspars (Melo et al, 1995;Batista et al, 2016). The non-exchangeable K is linked to the presence of expandable 2:1 clay minerals (Silva et al, 1995).…”
Section: Introductionmentioning
confidence: 99%